Viral Coinfection and Nasal Cytokines in Children With Clinically Diagnosed Acute Sinusitis - Santiago M. C. Lopez; Santiago M. C. Lopez; Santiago M. C. Lopez; Nader Shaikh; Monika Johnson; Hui Liu; Judith M. Martin; John V. Williams (Frontiers Media S.A., 2022)
Objective: Children with no pathogenic bacteria in the nasopharynx are unlikely to have acute bacterial sinusitis. We evaluated whether information on clinical presentation, viral co-detection, and mucosal cytokine levels could be used to predict presence of bacteria in the nasopharynx.Method: We obtained nasopharyngeal (NP) swabs from children diagnosed with acute sinusitis. NP swabs were processed for bacterial culture, viral PCR testing, and cytokine expression. We examined whether results of the bacterial culture could be predicted based on the presence of clinical information, presence of viruses or mucosal cytokine levels.Results: We enrolled 174 children; 123 (71%) had a positive culture for potentially pathogenic bacteria and 51 (29%) had normal flora. 122/174 (70%) tested positive for one or more viruses. Compared to children with normal flora, children with pathogenic bacteria were more likely to have viruses (p < 0.01), but this relationship disappeared when we adjusted for age. Children with pathogenic bacteria in their nasopharynx and children with normal flora had similar levels of nasal cytokines.Conclusion: In children with clinically diagnosed acute sinusitis, clinical presentation, levels of nasal cytokines, and presence of viruses do not differentiate children with and without pathogenic bacteria in their nasopharynx.